Ductility of brick masonry beams with containment reinforcement - Raghunath, S.; Rao, K.S. Nanjunda; Jagadish, K.S. (Journal of Structural Engineering, 2024)
The paper discusses an innovative way of reinforcing brick masonry perpendicular to the bed joints termed as ‘containment reinforcement’, to impart flexural ductility to the otherwise brittle masonry. The effectiveness of the concept has been examined through specially designed flexural tests on masonry beam elements. Totally 13 beams of thickness 225 mm (6 numbers) and 105 mm (7 numbers) with mild steel rods and galvanized iron wires as containment reinforcement have been tested under four point bending. Ultimate moment, deflection and curvature ductility have been obtained from the experiments. A theoretical analysis has been carried out following the principles employed for reinforced concrete sections to predict the moment-curvature relationship up to the ultimate. The investigation has shown significant curvature ductility values ranging from 9.5 to 23. The theoretical moment-curvature relation compares reasonably well with the experimental results.